Bangkok Technical Institute an institutional case study - Chareonpanich, Somchai 1938-
This is an institutional case study of Bangkok Technical Institute. Established in 1952, Bangkok Technical Institute is instituted by the Ministry of Education to improve the national program of vocational education in accordance with government policy.